2015
DOI: 10.1167/iovs.15-17050
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Crystalline Lens Volume During Accommodation in a Lens Stretcher

Abstract: Lens volume remains effectively constant during accommodation, with changes that are less than 1% on average. This result supports a hypothesis that the change in lens shape with accommodation is accompanied by a redistribution of tissue within the capsular bag without significant compression of the lens contents or fluid exchange through the capsule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 31 publications
(78 reference statements)
5
20
0
Order By: Relevance
“…In the accommodating eyes, we found that VOL remained constant with accommodation, DIA decreased and EPP shifted backwards, which is consistent with previously reported results by Hermans et al, 26 and Marussich et al 9 However, Gerometta et al 66 measured an increase of lens VOL with accommodation.…”
Section: Comparison With Earlier Worksupporting
confidence: 92%
See 2 more Smart Citations
“…In the accommodating eyes, we found that VOL remained constant with accommodation, DIA decreased and EPP shifted backwards, which is consistent with previously reported results by Hermans et al, 26 and Marussich et al 9 However, Gerometta et al 66 measured an increase of lens VOL with accommodation.…”
Section: Comparison With Earlier Worksupporting
confidence: 92%
“…These results are in agreement with recent studies that reveal the relevance of lens surface astigmatism 3,27 and errors associated to the assumption of lens rotational symmetry. 9 The proposed approach could be implemented in current commercial devices such as Scheimpflug-imaging based systems or clinical anterior segment OCT. Nevertheless, as demonstrated before, distortion correction is critical to obtain accurate results.…”
Section: Advantages Of 3d Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete recovery of fiber width is consistent with bulk lens equatorial recovery, which was also complete at 6%, and nearly complete at 9% equatorial strain. Since 9% equatorial strain is already beyond the physiological equatorial strain that accommodative lenses would experience in vivo (Jackson, 1907;Marussich et al, 2015), we did not examine the effect higher loads to determine whether greater equatorial strains led to incomplete recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Our data shows that compression with 10% axial strain in mouse lenses does not cause irreversible damage to bulk lens shape. Ten percent axial strain is within the range of physiological primate lens shape changes during accommodation calculated from in vivo measurements (Jackson, 1907;Doyle et al, 2013;Marussich et al, 2015). Thus, for the rest of this study, we focused primarily on the microstructural changes that occur at 10% axial strain.…”
Section: Bulk Lens Dimensions Recover Only Partially At Higher Strainsmentioning
confidence: 99%